DEVELOPMENT OF CHARACTER EDUCATION BASED ON TASAWUF AT AUTO MATSUDA VOCATIONAL SCHOOL - Suyana, Nana; Sugiharto, Sugiharto; Ismail, Ismail; Kusman, Agus; Mansur, Mansur (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
The background of this research departs from the need for a spiritual approach that is able to shape the character of students holistically amidst the challenges of vocational education that tends to be oriented towards technical skills. Purpose: This study aims to examine and develop a Sufism-based character education model at SMK Auto Matsuda, Kuningan, West Java. Method: This research uses the Research and Development (R&D) method with the Rowntree development model which includes three main stages, namely the planning stage, the development stage, and the evaluation stage. Result: The findings show that the integration of values ​​such as sincerity, patience, and humility through daily practices such as collective dhikr and role models has had a positive impact on the development of student character. Conclusion: The implications of this study indicate that the Sufism approach can be a strategic alternative in building the character of students with integrity, especially in vocational schools that demand mental and moral readiness in facing the world of work. This study recommends strengthening the spiritual curriculum and teacher training in understanding and implementing Sufism values ​​systematically.